Avaliação da aplicação da água residuária de fecularia em cultivo de Brachiaria brizantha cv MG-5 e seu impacto no solo - Soares, Doralice Aparecida Favaro (2009)
This experiment was carried out in an area of 5000 m2 situated in Cidade Gaucha, Parana State, Brazil, which coordinates are 23 ° 22 '48 "N, 52 ° 56' 42" W, to evaluate the impact of the application of cassava industry wastewater in a dystrophic Ultisol at an area that has been cultivated for two years with Brachiaria brizantha MG-5. The wastewater used was taken out of an existing treatment and applying system by using a sprinkler system with a 4,7 L s-1 flow and 30m wet radius. Three application ranges were chosen: T1=10mm, T2= 29,6mm e T3=36,6mm, beyond the control located out of the area reached by the sprinkler system. The wastewater was applied in two periods. The first one was from 11/20/2008 to 01/23/2009 and the second one was from 03/26/2009 to 05/15/2009. The applications were weekly, with four hours of duration each. The height of plant, COD, pH, electric conductivity and total, fixed and soluble solids from wastewater applied were monitored in each treatment monthly. At the end of the each period, the dry mass, the green mass and the height of the plant were determined and chemical analysis of the plant tissue were made for each treatment. It was also collected soil samples in each treatment, in layers of 20 cm to a depth of 100cm in order to do chemical analysis. The results shows that the pasture of Brachiaria brizanta cv MG-5 is a good potassium absorber and that in summer it is greater than in fall. There were no soil salinization observed in the study period. The levels of calcium, magnesium and potassium in the 0 to 40cm depth increased, and reduced levels of aluminum with the wastewater application. The potassium movement of the soil followed the distribution of application of water and nutrient by the water provided a good distribution of these nutrients along the profile studied.